2014
DOI: 10.1007/s00421-014-2822-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of objectively measured sedentary behavior, light activity, and markers of cardiometabolic health in young women

Abstract: Sedentary behavior and light physical activity were independently associated with markers of cardiometabolic health in young, adult women. Our data suggest that VO2peak and body composition may be important mediators of these associations. Decreasing sedentary behavior and increasing light physical activity may be important for maintaining cardiometabolic health in young, adult women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 59 publications
9
77
0
1
Order By: Relevance
“…Further analysis confirmed the strong association between objectively measured sedentary behavior and triglyceride levels, which was previously observed in individuals both with and without diabetes mellitus 10, 22, 30, 32, 34, 35. This is consistent with the potential mechanism that reduced skeletal muscle contractions from prolonged sedentary behavior may depress uptake of plasma triglycerides and triglycerides‐derived fatty acid into skeletal muscle through suppression of lipoprotein lipase activity 36, 37.…”
Section: Discussionsupporting
confidence: 85%
“…Further analysis confirmed the strong association between objectively measured sedentary behavior and triglyceride levels, which was previously observed in individuals both with and without diabetes mellitus 10, 22, 30, 32, 34, 35. This is consistent with the potential mechanism that reduced skeletal muscle contractions from prolonged sedentary behavior may depress uptake of plasma triglycerides and triglycerides‐derived fatty acid into skeletal muscle through suppression of lipoprotein lipase activity 36, 37.…”
Section: Discussionsupporting
confidence: 85%
“…Another study conducted by Kozakova et al on participants who were not involved in regular intensive exercise training and competitive sports activity reported that physical activity has no association with adiponectin (r = -0.08) (31). Green et al who investigated the associations between objectively measured physical activity, light activity, and markers of cardiometabolic health in young women showed that there were again showed no association between sedentary behaviour, light physical activity and moderate to vigorous physical activity with adiponectin, P > 0.05 (27).…”
Section: Relationship Between Physical Activity/exercise and Adipokinmentioning
confidence: 99%
“…Crosssectional and intervention studies were included which consisted of six cross-sectional studies and 12 intervention studies. Most articles were based on investigations in the United States of America (19,20,(27)(28)(29). It was obvious that most studies were conducted in developed countries since information was rather lacking from developing and under-developed countries.…”
Section: Articles Retrievedmentioning
confidence: 99%
See 2 more Smart Citations